Wave File Features Extraction using Reduced LBP - Aws Al-Qaisi; Saleh A. Khawatreh; Ahmad A. Sharadqah; Ziad A. Alqadi (International Journal of Electrical and Computer Engineering (IJECE), 2018)
In this work, we present a novel approach for extracting features of a digital wave file. This approach will be presented, implemented and tested. A signature or a key to any wave file will be created.  This signature will be reduced to minimize the efforts of digital signal processing applications. Hence, the features array can be used as key to recover a wave file from a database consisting of several wave files using reduced Local binary patterns (RLBP). Experimental results are presented and show that The proposed RLBP method is at least 3 times faster than CSLBP method, which mean that the proposed method is more efficient.